Synthesis and preliminary evaluation of 4-hydroxy-6-(3-[11C]methoxyphenethyl)pyridazin-3(2H)-one, a 11C-labeled d-amino acid oxidase (DAAO) inhibitor for PET imaging. Issue 16 (15th August 2020) - Deng, Xiaoyun; Zhang, Yiding; Chen, Zhen; Kumata, Katsushi; Van, Richard; Rong, Jian; Shao, Tuo; Hatori, Akiko; Mori, Wakana; Yu, Qingzhen; Hu, Kuan; Fujinaga, Masayuki; et al.
Graphical abstract: Highlights: We developed an efficient radiosynthetic route to a 11 C-labeled DAAO ligand (8 ). The radiosynthesis was achieved with high radiochemical yield and high molar activity. The DAAO PET ligand (8 ) demonstrated high in vitro binding specificity by autoradiography studies. Further optimization is necessary for improved brain penetration. Abstract: Selective DAAO inhibitors have demonstrated promising therapeutic effects in clinical studies, including clinically alleviating symptoms of schizophrenic patients and ameliorating cognitive function in Alzheimer's patients with early phase. Herein we report the synthesis and preliminary evaluation of a 11 C-labeled positron emission tomography ligand based on a DAAO inhibitor, DAO-1903 (8 ). 11 C-Isotopologue of 8 was prepared in high radiochemical yield with high radiochemical purity (>99%) and high molar activity (>37 GBq/µmol). In vitro autoradiography studies indicated that the ligand possessed high in vitro specific binding to DAAO, while in vivo dynamic PET studies demonstrated that [ 11 C]8 failed to cross the blood–brain barrier possibly due to moderate brain efflux mechanism. Further chemical scaffold optimization is necessary to overcome limited brain permeability and improve specific binding.